Active membranes: 3D printing of elastic fibre patterns on pre-stretched textiles. (March 2019) - Agkathidis, Asterios; Berdos, Yorgos; Brown, André
There has been a steady growth, over several decades, in the deployment of fabrics in architectural applications; both in terms of quantity and variety of application. More recently, three-dimensional printing and additive manufacturing have added to the palette of technologies that designers in architecture and related disciplines can call upon. Here, we report on research that brings those two technologies together – the development of active membrane elements and structures. We show how these active membranes have been achieved by laminating three-dimensional printed elasto-plastic fibres onto pre-stretched textile membranes. We report on a set of experimentations involving one-, two- and multi-directional geometric arrangements that take TPU 95 and polypropylene filaments and apply them to Lycra textile sheets, to form active composite panels. The process involves a parameterised design, actualised through a fabrication process including stress-line simulation, fibre pattern three-dimensional printing and the lamination of embossed patterns onto a pre-stretched membrane; followed by the release of tension afterwards in order to allow controlled, self-generation of the final geometry. Our findings document the investigation into mapping between the initial two-dimensional geometries and their resulting three-dimensional doubly curved forms. We also reflect on the products of the resulting, partly serendipitous, design process.